Innovative learning through Lesson Study for Learning Community (LSLC) in the manufacturing process course - Santosa, Irfan; Wibowo, Agus; Farid, Ahmad; Wilis, Galuh Rengganis; Sunardi, Sunardi; Saputra, Dicnanda Wildan (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Community Service Activities are designed to provide innovative and engaging educational experiences that align with the broader goals of teaching and learning in higher education. One such initiative is implemented through the Lesson Study for Learning Community (LSLC) model in collaboration with PT. Barata Indonesia, aiming to bridge the gap between theoretical instruction and the practical demands of the professional world. This community service program focuses specifically on the Manufacturing Process course, with a thematic emphasis on metal coating. The primary participants are 55 fourth-semester students enrolled in the 2024/2025 academic year. A qualitative approach is used to evaluate the enhancement of students’ knowledge and competencies. The findings indicate a high level of enthusiasm among students, with a 90% increase in understanding of metal coating concepts. Furthermore, students’ practical competencies were significantly strengthened through direct hands-on experience at PT. Barata Indonesia. Kegiatan Pengabdian Masyarakat dirancang untuk memberikan pengalaman pendidikan yang inovatif dan menarik yang sejalan dengan tujuan pengajaran dan pembelajaran yang lebih luas di pendidikan tinggi. Salah satu inisiatif tersebut dilaksanakan melalui model Lesson Study for Learning Community (LSLC) bekerja sama dengan PT. Barata Indonesia, yang bertujuan untuk menjembatani kesenjangan antara instruksi teoritis dan tuntutan praktis dunia profesional. Program pengabdian masyarakat ini berfokus secara khusus pada kursus Proses Manufaktur, dengan penekanan tematik pada pelapisan logam. Peserta utama adalah 55 mahasiswa semester empat yang terdaftar pada tahun akademik 2024/2025. Pendekatan kualitatif digunakan untuk mengevaluasi peningkatan pengetahuan dan kompetensi mahasiswa. Temuan menunjukkan tingkat antusiasme yang tinggi di antara mahasiswa, dengan peningkatan 90% dalam pemahaman konsep pelapisan logam. Selain itu, kompetensi praktis mahasiswa diperkuat secara signifikan melalui pengalaman langsung di PT. Barata Indonesia.